This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 18.100B, Fall 2002, Homework 10 Due by Noon, Thursday December 5 Rudin: (1) Chapter 7, Problem 14 Solution. There is a function f as described, just set ) t 1 3 1 f ( t ) = 3( t 1 3 t 2 3 ) 3 1 2 t 1 3 and for instance f (2 t ) = f ( t ) for 1 t 2 and then f (2 k + t ) = f ( t ) for all k N , k = 0 , t [0 , 2] . This gives a continuous function. Consider (1) x ( t ) = 2 n f (3 2 n 1 t ) , y ( t ) = 2 n f (3 2 n t ) . n =1 n =1 The n th term in the series for (1) is bounded  2 n f (3 2 n 1 t )  2 n . By Theorem 7.10, the series converges uniformly. Thus x ( t ) is continuous by Theorem 7.12. The same argument applies to y ( t ) so ( t ) = ( x ( t ) , y ( t )) is continuous by Theorem 4.10. Now, to see that is surjective, follow the hint. Each point in [0 , 1] has a dyadic decomposition x = 2 n b n , b n = or 1 . n =1 Indeed one can compute the successive b n , n = 1 , . . . , k to arrange that k x 2 n b n 2 k . Then choose b k +1 = or 1 depending on whether n =1 k k < 2 k 1 x 2 n b n or 2 k 1 x 2 n b n 2 k . Now we let n =1 n =1 the a 2 n 1 be these numbers for x and a 2 n those for y ....
View
Full
Document
This note was uploaded on 12/16/2011 for the course STAT 5446 taught by Professor Frade during the Fall '09 term at FSU.
 Fall '09
 Frade

Click to edit the document details